Role of Lumbar Puncture in Late Onset Neonatal Sepsis - Das, Amit Kumar; Mishra, Deepak; Jha, Nitu Kumari; Mishra, Rakesh; Jha, Soniya (Journal of Nepal Paediatric Society, 2019)
Introduction: Neonatal sepsis is a clinical syndrome characterized by signs and symptoms of infection with or without accompanying bacteremia in the first month of life. It is responsible for about 30-50% of the total neonatal deaths in developing countries. Neonatal sepsis can be divided into two sub-types depending upon whether the onset of symptoms within the first 72 hours of life (Early Onset Neonatal Sepsis) or after 72 hours of life (Late Onset Neonatal Sepsis ). Meningitis is an important complication of late onset neonatal sepsis. Method: This was hospital based prospective observational study conducted among the neonates admitted with diagnosis of late onset neonatal sepsis in Neonatal Intermediate Care Unit (NIMCU) and Neonatal Intensive Care Unit (NICU) of Kanti Children’s Hospital from July 2016 to June 2017. The objective of this study was to evaluate the importance of performing LP in neonates with LONS. Results: 16.8% neonates with late onset neonatal sepsis were found to have meningitis. Among the neonates with meningitis CRP was positive 57.2% and negative in 42.8 %. Among the cases with abnormal CSF findings, blood culture was sterile in 85% cases and organism was isolated 15% cases. In 88.8% cases with positive blood culture, no meningitis was detected. Lumbar puncture was traumatic in 1 neonate (0.8%) in first attempt. Apart from this no other complication of performing lumbar puncture was noted. Conclusion: Lumbar puncture and CSF examination is mandatory in all cases with late-onset sepsis.